Effects of bed rest on physical performance in athletes: a systematic and narrative review - Spiering, B. A.; Weakley, J.; Mujika, I. (Sports Medicine, 2023)
Background: Athletes can face scenarios in which they are confined to bed rest (e.g., due to injury or illness). Existing research in otherwise healthy individuals indicates that those entering bed rest with the greatest physical performance level might experience the greatest performance decrements, which indirectly suggests that athletes might be more susceptible to the detrimental consequences of bed rest than general populations. Therefore, a comprehensive understanding of the effects of bed rest might help guide the medical care of athletes during and following bed rest. Objective: This systematic and narrative review aimed to (1) establish the evidence for the effects of bed rest on physical performance in athletes; (2) discuss potential countermeasures to offset these negative consequences; and (3) identify the time-course of recovery following bed rest to guide return-to-sport rehabilitation. Methods: This review was performed using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Four databases were searched (SPORTDiscus, Web of Science, Scopus, and MEDLINE/PubMed) in October of 2022, and studies were included if they were peer-reviewed investigations, written in English, and investigated the effects of horizontal bed rest on changes in physical capacities and qualities in athletes (defined as Tier 3-5 participants). The reporting quality of the research was assessed using a modified version of the Downs & Black checklist. Furthermore, findings from studies that involved participants in Tiers 1-2 were presented and synthesized using a narrative approach. Results: Our systematic review of the literature using a rigorous criterion of `athletes` revealed zero scientific publications. Nevertheless, as a by-product of our search, seven studies were identified that involved apparently healthy individuals who performed specific exercise training prior to bed rest. Conclusions: Based on the limited evidence from studies involving non-athletes who were otherwise healthy prior to bed rest, we generally conclude that (1) bed rest rapidly (within 3 days) decreases upright endurance exercise performance, likely due to a rapid loss in plasma volume; whereas strength is reduced within 5 days, likely due to neural factors as well as muscle atrophy; (2) fluid/salt supplementation may be an effective countermeasure to protect against decrements in endurance performance during bed rest; while a broader array of potentially effective countermeasures exists, the efficacy of these countermeasures for previously exercise-trained individuals requires further study; and (3) athletes likely require at least 2-4 weeks of progressive rehabilitation following bed rest of = 28 days, although the timeline of recovery might need to be extended depending on the underlying reason for bed rest (e.g., injury or illness). Despite these general conclusions from studies involving non-athletes, our primary conclusion is that substantial effort and research is still required to quantify the effects of bed rest on physical performance, identify effective countermeasures, and provide return-to-sport timelines in bona fide athletes.